PENERAPAN MODEL DISCOVERY LEARNING SECARA VIRTUAL UNTUK MENINGKATKAN HASIL BELAJAR IPA MATERI KEMAGNETAN PADA SISWA SMP - Fira Amalia Qonita Firdaus; Mohammad Budiyanto; Enny Susiyawati (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2023)
This study was aimed to describe the result of virtual discovery learning model implementation in improving learning outcomes of Junior High School students on magnetism. The study involved 30 students of 9th grade at one of Public Junior High School in Probolinggo City. This study used One Group Pretest-Posttest Design as a research model. The analytical technique was analyzation of learning outcomes by using N-Gain. This study’s impact was the improvement of student learning outcomes that indicated through the result of N-Gain after analyzing pretest and posttest scores. The posttest score gained average score that higher than pretest average score, so that, the average of N-gain class gained high category. Based on the impact, it can be concluded that the implementation of virtual discovery learning model improved junior high school student learning outcomes on magnetism.